1996
DOI: 10.1007/bf02529137
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical demonstration of GABAB receptors in the rat gastrointestinal tract

Abstract: Immunohistochemical localization of GABA(B)-receptors was demonstrated in the rat gastrointestinal tract using a monoclonal antibody (GB-1) raised against the purified GABA(B)-receptor. Immunoreactive staining for GABA(B)-receptors was found in some populations of endocrine, muscular and neuronal components in the stomach and gut wall. Positive mucosal epithelial, probably endocrine, cells were distributed throughout the stomach and intestine. Double immunostaining indicated that such positive cells for GABA(B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…The amount of a neurochemical, such as GABA for example, found within, or produced by, probiotics is most likely sufficient to influence localized immune and neurophysiological process in the gut as both immune and neuronal cells have been well documented to respond to nanomolar concentrations of GABA [31,32,[37][38][39]. The delivery of neurochemicals by probiotics may therefore either be in the amount already contained in the bacterium at time of ingestion or that which is actively produced once inside the gastrointestinal tract.…”
Section: Testing the Hypothesismentioning
confidence: 97%
“…The amount of a neurochemical, such as GABA for example, found within, or produced by, probiotics is most likely sufficient to influence localized immune and neurophysiological process in the gut as both immune and neuronal cells have been well documented to respond to nanomolar concentrations of GABA [31,32,[37][38][39]. The delivery of neurochemicals by probiotics may therefore either be in the amount already contained in the bacterium at time of ingestion or that which is actively produced once inside the gastrointestinal tract.…”
Section: Testing the Hypothesismentioning
confidence: 97%
“…While this does not prove that GABA was not involved in the anti-nociceptive effects of oral ingestion of lactobacilli, since we have no way of determining how much GABA was synthesized in situ in the intestine, it does nevertheless cast some doubt on this being the mechanism of analgesic effect we have seen. Nevertheless, GABA is synthesized within the intestinal lumen, and some bacteria even have the capacity to selectively take up GABA from the environment through a GABA-like receptor (Guthrie & Nicholson-Guthrie, 1989) and others have shown that GABA, as well as its receptor are routinely expressed within the intestinal epithelium (Nakajima, Tooyama, Kuriyama, & Kimura, 1996), so it is reasonable to assume that local effects of locally synthesized neurotransmitters are playing some physiological roles, in all aspects of interkingdom signaling, bacteria-bacteria communication and also bacteria to host interactions.…”
Section: Microbial Neuroendocrinologymentioning
confidence: 98%
“…GABA and its ionotropic and metabotropic receptors are widely distributed throughout the ENS, in both submucosal and myenteric neurons, from the stomach to the ileum (Auteri et al, 2015). In addition, Nakajima et al (1996) reported the expression of GABA B receptors in cells morphologically similar to EECs, where they co-localized with cells containing somatostatin (in the stomach) or serotonin (in the duodenum). However, a later study failed to detect any positive EEC for GABA B receptors (Casanova et al, 2009).…”
Section: Glu/gaba: Receptors Signaling and Transportmentioning
confidence: 99%